HASIL PENGOLAHAN MOBIL PENGOLAH AIR BERSH DALAM PENYEDIAAN AIR BERSIH DAN AIR MINUM UNTUK LAYANAN BENCANA - Mariya Ulfa; Margono .; Bambang Sunarko (Poltekkes Kemenkes Surabaya, 2013)
Water can be regarded as one of the sources of life. The absence of water maythreaten the very survival of the ecosystems and all living creatures. In addition to dailyconsumption, water is also used for bathing and washing. Normally, water can easily beobtained provided there is no special event such as a natural disaster, where victims of suchemergency will suffer from lack of potable or drinking water, despite the amount of aidsprovided by the government. Among other things, the government have introduced a mobilewater treatment unit. This study was aimed at understanding the efficiency of such a mobileunit in providing water in disaster areas.This was a descriptive study to present results of field observations and other datagathering methods in tables and other forms for comparison with relevant and appropriatestandards. In addition to field observations data collection was carried out through interviewsand measurements. The object under study was a mobile treatment unit owned and operatedby the Badan Penanggulangan Bencana Oaerah (BPBO).Results of the investigation indicated that the mobile unit was being operated inefficient and effective manners in satisfying the need and demand for potable and drinkingwater. The treatment system in the mobile unit relied on Reversed Osmoses (RO) processes.The amount of water generated by this unit was 1000 L/hour for potable water and 600 L/hourfor drinking water. Results of the microbiological, physical and chemical examinations havesatisfied the designated requirements and standards.The study suggested that all relevant staff should be able to operate the unit, as well asinitiating manageable repairs when such things are called for. Minor problems pertaining to theunit can be solved on site and this may lessen the dependence on ouside assistance. The unitworks quite well, therefore efforts should be directed at managing supplies, maintenance, andto provide pretreatment unit to improve unit's capability to treat raw water having turbidity ofmore than 30 NTU.Keywords: disaster, emerpency. mobile water treament unit